Touch and Affect in Alice Munro’s “Nettles”; or, Redefining Intimacy - Lorre-Johnston, Christine (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
The skin, and the sense of touch it is linked with, is often an essential way to approach the world in Munro’s stories, and brings the focus onto affects. This study focuses on touch and the skin in “Nettles” (Hateship, Friendship, Courtship, Loveship, Marriage, 2001), a particularly luminous instance of story in which skin and affect together play a key role in creating a sense of intimacy.